ANALISIS PENGARUH WORK FAMILY CONFLICT DAN FAMILY WORK CONFLICT TERHADAP EMPLOYEE PERFORMANCE DENGAN EMOTIONAL EXHAUSTION SEBAGAI VARIABEL INTERVENING (Studi pada Karyawan Berstatus Menikah pada PT. PLN (Persero) Unit Induk Distribusi Jawa Tengah dan Daerah Istimewa Yogyakarta) - Nur Azliah, Devita Septi; Lataruva, Eisha (Faculty of Economics and Business Diponegoro University, 2021)
ABSTRACT This study aims to analyze and determine the effect of work family conflict and family work conflict on employee performance through emotional exhaustion as an intervening variable at PT. PLN (Persero) on Distribution Main Unit of Central Java and Yogyakarta Special Region. The population in this study is all of employees. The number of samples used in this study were 65 respondents, with characteristc employees who are married. Data was collected through the distribution of questionnaires on samples selected through non-probability sampling techniques with purposive sampling method. Measurements in the questionnaires using a Likert Scale. Five hypotheses on study were tested using quantitative methods and data analyze techniques with path analysis and multiple linear regression analysis method with SPSS 25.0 software. The results of the statistical test analysis indicate that work family conflict variable has a significant positive effect on emotional exhaustion, and has a significant negative effect on employee performance. Family work conflict variable has a significant positive effect on emotional exhaustion and and has a significant negative effect on employee performance. In addition, it is also proven that emotional exhaustion variable can mediate the relation between work family conflict and family work conflict on employee performance.